Sub-Saharan Africa : growth, savings, and investment, 1986-93 - Hadjimichael, Michael T.; Ohio Library and Information Network (Washington, DC : International Monetary Fund, 1995)
This paper assesses the economic performance during 1986-93 of sub-Saharan African countries as a group and of selected analytical subgroups of countries
"January 1995."
Available in PDF, ePUB, and Mobi formats on the Internet
English
Keywords: Saving and investment; Africa, Sub-Saharan -- Economic conditions -- 1960-; Africa, Sub-Saharan--Economic policy; Saving and investment Africa, Sub-Saharan